AAZTA: An Ideal Chelating Agent for the Development of 44Sc PET Imaging Agents1. (18th January 2017) - Nagy, Gábor; Szikra, Dezső; Trencsényi, György; Fekete, Anikó; Garai, Ildikó; Giani, Arianna M.; Negri, Roberto; Masciocchi, Norberto; Maiocchi, Alessandro; Uggeri, Fulvio; Tóth, Imre; Aime, Silvio; et al.
Abstract: Unprecedented fast and efficient complexation of Sc III was demonstrated with the chelating agent AAZTA (AAZTA=1, 4‐bis(carboxymethyl)‐6‐[bis(carboxymethyl)]amino‐6‐methylperhydro‐1, 4‐diazepine) under mild experimental conditions. The robustness of the 44 Sc(AAZTA) − chelate and conjugated biomolecules thereof is further shown by in vivo PET imaging in healthy and tumor mice models. The new results pave the way towards development of efficient Sc‐based radiopharmaceuticals using the AAZTA chelator.